2013
DOI: 10.1093/mnrasl/slt108
|View full text |Cite
|
Sign up to set email alerts
|

A submillimetre-bright z ∼ 3 overdensity behind a z ∼ 1 supercluster revealed by SCUBA-2 and Herschel

Abstract: We present a wide-field (30 arcmin diameter) 850 μm Submillimetre Common-User Bolometer Array-2 map of the spectacular three-component merging supercluster, RCS 231953+00, at z = 0.9. The brightest submillimetre galaxy (SMG) in the field (S850 ≈ 12 mJy) is within 30 arcsec of one of the cluster cores (RCS 2319–C), and is likely to be a more distant, lensed galaxy. Interestingly, the wider field around RCS 2319–C reveals a local overdensity of SMGs, exceeding the average source density by a factor of 4.5, with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
5
8
0
Order By: Relevance
“…Our observations of the region around HATLAS12-00 have uncovered a number of potentially associated sources at both submm wavelengths, as found by SCUBA2 and LABOCA, and in the Herschel data themselves. These results are not dissimilar to the submm source overdensities uncovered by Stevens et al (2010) around quasars, the Herschel source overdensities found by Rigby et al (2014) around some high redshift radio galaxies, the overdensity of Herschel and LABOCA sources associated with the Spiderweb galaxy (Dannerbauer et al, 2014), or the Herschel and SCUBA2 overdensity found behind the RCS 231953+00 supercluster by Noble et al (2013). We here quantitatively asses the source overdensities of both submm and Herschel sources around HATLAS12-00.…”
Section: Source Overdensities Around Hatlas12-00supporting
confidence: 81%
See 3 more Smart Citations
“…Our observations of the region around HATLAS12-00 have uncovered a number of potentially associated sources at both submm wavelengths, as found by SCUBA2 and LABOCA, and in the Herschel data themselves. These results are not dissimilar to the submm source overdensities uncovered by Stevens et al (2010) around quasars, the Herschel source overdensities found by Rigby et al (2014) around some high redshift radio galaxies, the overdensity of Herschel and LABOCA sources associated with the Spiderweb galaxy (Dannerbauer et al, 2014), or the Herschel and SCUBA2 overdensity found behind the RCS 231953+00 supercluster by Noble et al (2013). We here quantitatively asses the source overdensities of both submm and Herschel sources around HATLAS12-00.…”
Section: Source Overdensities Around Hatlas12-00supporting
confidence: 81%
“…no other region in our 10000 comparison fields has a similar 350µm source density), < 10 −4 , 8 × 10 −4 , 3 × 10 −4 and 3 × 10 −4 levels, suggesting the possible presence of an overdensity on larger scales than the Planck beam, up to a radius of ∼10 arcmin. While this would certainly be a large structure in terms of physical size, amounting to about 10Mpc in diameter if it lies at the same redshift as HATLAS12-00, it is comparable to the scale of the z∼3 candidate supercluster identified by Noble et al (2013), through a combination of SPIRE and SCUBA2 data, and a number of other known protoclusters (Casey, 2016). Examination of the progenitors of z = 0 massive clusters in the Millennium Simulation (Diener et al, 2015) suggests that they can be as large as 20Mpc across at z ∼ 3, consistent with the sizes of these overdensities identified in the far-IR/submm.…”
Section: Spire Source Densitymentioning
confidence: 91%
See 2 more Smart Citations
“…The use of Herschel -SPIRE colour-colour diagrams to separate sources of different redshifts is well established (e.g. Herranz et al 2013;Noble et al 2013;Clements et al 2014;Ivison et al 2016;Negrello et al 2016), though the precise interpretation of the results are uncertain. Typically, sources whose SED peak at longer wavelengths tend to lie at higher redshifts ( 2016; Ivison et al 2016), and therefore sources whose SED peak at 250, 350 and 500 µm likely indicate progressively higher redshifts.…”
Section: Herschel Coloursmentioning
confidence: 99%